The relative pricing of U.S. Treasury STRIPS: empirical evidence - Jordan, Bradford D; Jorgensen, Randy D; Kuipers, David R (Journal of Financial Economics, 2000)
We investigate pricing relations and the potential for arbitrage in the U.S. Treasury STRIPS market, stressing the importance of reconciling quoted Treasury data with actual market pricing conventions. We document that stripping and reconstitution profits in the STRIPS market are fleeting and rarely economically significant; that matched-maturity principal and coupon STRIPS generally have different prices due, at least in part, to richness or cheapness in the underlying note or bond; and that apparent negative forward rates in the STRIPS market are concentrated in certain long-maturity STRIPS that do not actually exist at the time.